Serum Uric Acid Levels at Admission Could Predict the Chronic Post-stroke Fatigue - Ren, Wenwei; Wu, Junxin; Wu, Zijing; Yang, Shuang; Jiang, Xiaofang; Xu, Minjie; Wu, Beilan; Xie, Caixia; He, Jincai; Yu, Xin (Frontiers in Nutrition, 2022)
Background: Post-stroke fatigue (PSF) is a frequent complication of stroke. Serum uric acid (SUA) is frequently thought to be a risk factor for stroke. This study aimed to investigate whether SUA also played a role in PSF. Methods: Subjects with ischemic stroke were screened from The First Affiliated Hospital of Wenzhou Medical University between January 2020 and October 2020. Patients' fatigue symptoms were assessed by the Fatigue severity scale (FSS). To investigate the relationship between SUA and PSF, binary logistic regression analysis was conducted, with the confounders being controlled. SUA levels were divided into four layers (Q1 ≤245 μmol/L; Q2 246-308 μmol/L; Q3 309-365 μmol/L; Q4 ≥366μmol/L) based on the quartiles. Results: SUA levels were significantly higher in the PSF group (345.96 ± 73.78 μmol/L) than the non-PSF group (295.97 ± 87.8 μmol/L, P<0.001). There were no differences in any other variables between these two groups. After adjusting the confounders, the risk of PSF in Q4 layer（≥366μmol/L）was 5.29 times (95% CI 1.61-17.32, P=0.006) higher than that in Q1 (≤245 μmol/L). Conclusion: High SUA at admission was an independent risk factor for fatigue one year after stroke onset. High SUA（≥366μmol/L）during stroke deserves more attention, and active control of high SUA levels may be beneficial to reduce the incidence of PSF in the chronic stage following stroke.